Makrozonasi dan Mikrozonasi Kerentanan Bencana Gempa Bumi di Wilayah Ende sebagai Data dasar Perencanaan dan Pengembangan Wilayah - Saputra, Sukahar Eka; Suhaimi, A.; Mulyasari, F. (Geological Agency, 2010)
DOI: 10.17014/ijog.v5i3.101The application of macrozonation and microzonation on earthquake hazard susceptibility for zoning regulation in the regency and city levels, is one of the activities of joint technical cooperation between the Geological Agency, Ministry of Energy and Mineral Resources and the German Federal Institute for Geosciences and Natural Resources (BGR) which involved the local government of Ende. Macrozonation of the Ende Regency contains a basic information of seismotectonics which consists of geological conditions (geomorphology, lithology, structural geology, and neotectonics) and seismicities (epicenter distribution, focal mechanism, earthquake source zones, and accelerations of hard, intermediate and soft rocks as well as their maximum intensity). On the other sides, it includes administrative boundaries and potential earthquake hazards as well as its collateral hazards when the earthquakes occurred. The research in the city area was a microzonation parameters of amplification, predominant period, and susceptibility index of earthquake hazard and its combinations. These important parameters can be used as spatial planning data for an earthquake risk assessment at each zone based on it own susceptibility degree.